Pengaruh Gaya Kepemimpinan Islam Terdadap Etos Kerja Karyawan Di PT. Bank Muamalat Kc. Darmo Surabaya - Ali Mufrodi; Rizki Via Andriani (Universitas Muhammadiyah Surabaya, 2023)
Abstract This research is motivated by the role of Islamic leadership style in improving the work ethic of employees of a company. Where leadership style is a very big determinant of the performance of a company. If the company has a leadership style that upholds morality and religion and is relevant to the times, it will improve a good work ethic and be able to utilize human resources wisely. The main problem that will be discussed in this study is the influence of Islamic leadership style on the work ethic of the employees at Muamalat Bank BO. Darmo Surabaya. Keywords: The Influence of Islamic Leadership Style, Work Ethic.